183k views
1 vote
Which of the following equations is in equation formed when completing the square on y^2 - 12 y= -27

(y-6)^2=-27
(y+6)^2=9
(y-6)^2=9​

User Blagoh
by
4.7k points

1 Answer

5 votes

Answer:


(y-6)^2=9

Explanation:

Given


y^2 - 12y = -27

Required

Get equivalent expression using completing the square

Follow these steps:

  • Take the coefficient of y; That is -12
  • Divide it by 2; That is (-12/2)
  • Square it: (-12/2)^2

Add to both sides of the equation


y^2 - 12y + ((-12)/(2))^2= -27 + ((-12)/(2))^2


y^2 - 12y + (-6)^2= -27 + (-6)^2


y^2 - 12y + 36= -27 + 36


y^2 - 12y + 36= 9

Expand the right-hand side


y^2 - 6y - 6y + 36= 9

Factorize:


y(y-6)-6(y-6) =9


(y-6)(y-6)=9


(y-6)^2=9

User Jamie Pate
by
4.9k points